2017
DOI: 10.1111/bcpt.12702
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Increases Ventricular Vulnerability in an Experimental Whole‐Heart Model

Abstract: The traditional gout medication colchicine has been reported to effectively prevent atrial fibrillation recurrence after atrial fibrillation ablation or cardiac surgery in a few clinical trials. Severe adverse events have not yet been reported. The aim of the present study was to assess possible direct electrophysiological effects in an experimental whole-heart model. Ten rabbit hearts were isolated and Langendorff-perfused. Thereafter, colchicine was administered in two concentrations (1 and 3 μM). Eight endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…However, it, too, should be used with caution in patients with severe renal dysfunction and is contraindicated in patients on dialysis. An increase in ventricular vulnerability was shown in experimental models 826 …”
Section: Non‐cardiovascular Comorbiditiesmentioning
confidence: 95%
“…However, it, too, should be used with caution in patients with severe renal dysfunction and is contraindicated in patients on dialysis. An increase in ventricular vulnerability was shown in experimental models 826 …”
Section: Non‐cardiovascular Comorbiditiesmentioning
confidence: 95%
“…The efficacy of colchicine is significantly affected by the interruption rate of treatment. A study confirmed that using colchicine to treat cardiovascular disease increased the risk of adverse gastrointestinal reactions and myalgia but has no significant relationship with other adverse reactions ( Frommeyer et al, 2017 ). In addition, acute infusion of colchicine can increase the incidence of ventricular tachyarrhythmias in cardiac models ( Kirchhof et al, 2016 ).…”
Section: Use Of Colchicine In Cardiovascular Diseasementioning
confidence: 99%
“…Rare side effects include hepatic injury, rhabdomyolysis, hypersensitivity, and blood disorders. Major interactions are with statins and cytochrome P450 3A4 inhibitors [3,[22][23][24][25][26][27]. It acts by microtubule depolymerization and tubulin binding, inhibiting the NLRP3 inflammasome protein complex [28,29].…”
Section: Role Of Colchicinementioning
confidence: 99%